Evaluation de l’effet antifongique de l’huile essentielle de Rubus fruticosus sur Colletotrichum gloeosporioides agent de l’anthracnose de la tomate - NOUGAR, ASMA; DRISS, HAKIMA (My University, 2021)
Tomato anthracnose caused by the fungus Colletotrichum gloeosporioides is one of the major constraints on production. The present study aims to investigate the effect of Rubus fruticosus essential oil on "in vitro" mycelial growth and "in vivo" development on tomato leaves. The results obtained show that Rubus fruticosus EO demonstrated an average inhibitory effect at doses of 1% and 0.5%, so no total inhibition of mycelial growth. The results of the "in vivo" test, demonstrate the ineffectiveness of the essential oil of Rubus fruticosus, at the dose tested, to inhibit the development of anthracnose on the tomato plants tested.
Keywords: Antifungal activity, essential oil, Rubus fruticosus, Colletotrichum gloeosporioides, tomato.